The physiological closure of ductus arteriosus in the rat. An ultrastructural study - Jarkovská, D; Janatová, T; Hruda, J; Ostádal, B; Samánek, M (Anatomy and embryology, 1989)
The evolution of morphological changes in the wall of the ductus arteriosus during its physiological closure in newborn rats was examined by electron microscopy. The contraction of smooth muscle cells in the tunica media seems to be the primary mechanism which leads to the physiological closure of the ductus arteriosus. For this reason our attention was centred mainly on the morphology of the tunica media. No important changes in the ultrastructure of smooth muscle cells can be observed in the early phases of the closure. Most of them exhibit ultrastructural features of cells with enhanced synthetic activity during all phases of the closure. The permanent contraction of smooth muscle cells results in their morphological changes. The most striking is the herniation of smooth muscle cell cytoplasm into the endothelial and later into adjoining muscle cells. These changes together with signs of degeneration of the smooth muscle cells are already clearly discernible 120 min after birth. The elastic component of the tunica media exhibits surprisingly fast changes. As soon as 60 min after birth, the fragmentation of elastic membranes and their structural changes provided evidence about the degradation of elastic material. The matrix vesicles, probably derived from the lysosomal apparatus of the muscle cells, may play an essential role in this process.
Keywords: svalová kontrakce; krysa rodu Rattus; Muscle Contraction; Microscopy, Electron; Animals; ductus arteriosus; inbrední kmeny potkanů; Rats; Muscle, Smooth; Ductus Arteriosus; Heart; průchodnost cév; zvířata; Vascular Patency; srdce; Rats, Inbred Strains; hladké svalstvo; elektronová mikroskopie